Monte Carlo Simulation Strategies for Predicting CO/CH Adsorption onto Activated Carbons from Pure Gas Isotherms - José C.A. de Oliveira; Rafael B. Rios; Raúl H. López; Hugo R. Peixoto; Valéria Cornette; A. Eurico B. Torres; Célio L. Cavalcante; Diana C.S. Azevedo; Giorgio Zgrablich (Adsorption Science & Technology)
The problem of predicting the adsorptive properties of activated carbon (AC) towards a mixture of gases from the simple knowledge of the adsorption properties of the pure components is addressed, with special reference to the CO 2 /CH 4 mixture. The adsorption process for the pure gases and their mixtures was simulated using the Grand Canonical Monte Carlo (GCMC) method and the calculations were then used to analyze experimental isotherms for the pure gases and for mixtures with different molar fractions in the gaseous phase. It was shown that the pore-size distributions (PSDs) “sensed” by each of the pure probe gases was different one from the other and also from the PSDs “seen” by the mixture. A mixing rule for combining the PSDs corresponding to the pure gases is proposed for obtaining predictions regarding the adsorption of the corresponding mixtures, which are then compared with those arising from the classical IAST approximation. For this purpose, selectivity curves for CO 2 relative to CH 4 have been calculated and compared with experimental values. It was concluded that, for the adsorbate/adsorbent system under study, the proposed GCMC mixed model was capable of predicting the binary adsorption equilibrium, and especially the selectivity, more accurately than the IAST.